Macro- and microhemodynamic disorders as cardiovascular risk factors in overweight young people - Zh. V. Dzampaeva; E. A. Takoeva (Acta Biomedica Scientifica, 2022)
Obesity is associated with a high risk of cardiovascular diseases. Therefore, an urgent task of preventive medicine is to search for markers indicating the early development of cardiovascular pathology in young people in order to develop preventive measures.The aim of the study. To study macro- and microhemodynamics in young people with normal and elevated body mass index (BMI).Methods. After receiving informed consent, we evaluated microhemodynamics using Doppler ultrasound (Angiodin-PC (BIOSS, Russia); 16 MHz sensor) and macrohemodynamics by daily blood pressure monitoring (MnSDP-3 (BPLab, Peter Telegin LLC, Russia)) in students (20.05 ± 1.46 years old) who did not play sports in the period from 2019 to 2021. The subjects were divided into 2 groups according to their BMI: group 1 (control) – BMI ≤ 25 (average age 20.5 ± 0.7 years; average weight 59.47 ± 8.26 kg); group 2 – BMI ≥ 25 (average age 20.12 ± 1.73 years; average weight 83.8 ± 9.59 kg).Results. It has been proven that already at a young age, an increased BMI adversely affects the elasticity of the vascular wall. We registered a statistically significant increase in the peripheral resistance index (RI; Purcello index) (p = 0.022,) and the Stewart index (SD) (p = 0.0034) which are reflecting vascular wall remodeling. There is also a statistically significant increase in average blood pressure per day, day/night against the background of increased BMI. An insufficient degree of nocturnal decrease in systolic blood pressure is revealed, as well as an increase in pressure load and blood pressure variability.Conclusion. Since changes in the structure and function of the vessels of the microcirculatory bed are a precursor to preclinical disorders of systemic blood flow, the introduction of high-frequency Doppler ultrasound into the protocol of examination of people having metabolic syndrome will allow us to assess the functional status of large and small arteries and to identify early vascular disorders.